2006
DOI: 10.1161/01.res.0000219899.93384.ed
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin, the Proteolytic Fragment of Collagen XVIII, Induces Vasorelaxation

Abstract: Abstract-Collagen XVIII is an important component of the extracellular matrix and is expressed in basement membranes.Its degradation results in the generation of endostatin claimed to possess antiangiogenic activity. To date, only limited knowledge exists with regard to the cellular signaling of this molecule. We show in single-cell measurements using the Ca 2ϩ indicator fura-2 acetoxy methylester (fura-2 AM) and the nitric oxide (NO) indicator 4,5-diaminofluorescein diacetate that application of endostatin (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
54
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 39 publications
3
54
0
3
Order By: Relevance
“…These cell types regulate vascular tone and BP. This finding is consistent with previous studies showing that ES induces NO release by cultured endothelial cells and relaxation of ex vivo vascular rings (29,30). Further, we show that circulating nitrate levels were higher in ES-treated mice than in controls (Fig.…”
Section: Es Prevents Anti-vegf Antibody-induced Bp Elevations In C57bl/6supporting
confidence: 94%
See 4 more Smart Citations
“…These cell types regulate vascular tone and BP. This finding is consistent with previous studies showing that ES induces NO release by cultured endothelial cells and relaxation of ex vivo vascular rings (29,30). Further, we show that circulating nitrate levels were higher in ES-treated mice than in controls (Fig.…”
Section: Es Prevents Anti-vegf Antibody-induced Bp Elevations In C57bl/6supporting
confidence: 94%
“…This result is consistent with other studies showing that short-term exposure of bovine aortic endothelial cells to ES induced events associated with eNOS activation (30). Using single-cell measurements, Wenzel et al (29) showed that ES induced increases in NO production by human and murine endothelial cells that were blocked by an eNOS inhibitor. Ex vivo studies showing vessel relaxation suggested that this mechanism might be physiologically relevant.…”
Section: Es Prevents Anti-vegf Antibody-induced Bp Elevations In C57bl/6supporting
confidence: 91%
See 3 more Smart Citations